Development of a “turn off” fluorescent molecularly imprinted nanoparticle-based sensor for selective captopril quantification in synthetic urine and wastewater samples - Silva, Weida Rodrigues; Oliveira, Lara Fábia Magalhães; Sotomayor, Maria del Pilar Taboada [UNESP]; Petruci, João Flávio da Silveira (Springer Nature, 2024)
The combination of silica nanoparticles with fluorescent molecularly imprinted polymers (Si-FMIPs) prepared by a one-pot sol-gel synthesis method to act as chemical sensors for the selective and sensitive determination of captopril is described. Several analytical parameters were optimized, including reagent ratio, solvent, concentration of Si-FMIP solutions, and contact time. Fourier-transform infrared spectroscopy (FT-IR), transmission electron microscopy (TEM), and the ninhydrin assay were used for characterization. The selectivity was evaluated against molecules belonging to other drug classes, such as fluoroquinolones, nonacid nonopioids, benzothiadiazine, alpha amino acids, and nitroimidazoles. Under optimized conditions, the Si-FMIP-based sensor exhibited a working range of 1–15 µM, with a limit of detection (LOD) of 0.7 µM, repeatability of 6.4% (n = 10), and suitable recovery values at three concentration levels (98.5% (1.5 µM), 99.9% (3.5 µM), and 99.2% (7.5 µM)) for wastewater samples. The sensor provided a working range of 0.5–15 µM for synthetic urine samples, with an LOD of 0.4 µM and a repeatability of 7.4% (n = 10) and recovery values of 93.7%, 92.9%, and 98.0% for 1.0 µM, 3.5 µM, and 10 µM, respectively. In conclusion, our single-vessel synthesis approach for Si-FMIPs proved to be highly effective for the selective determination of captopril in wastewater and synthetic urine samples. Graphical abstract: (Figure presented.)
Keywords: Captopril; Fluorescence detection; Molecularly imprinted polymers; One-pot synthesis; Potential emerging pollutants